Multifocal visual evoked potentials in chronic inflammatory demyelinating polyneuropathy. Issue 8 (7th July 2018) - Graf, Jonas; Jansen, Lea; Ingwersen, Jens; Ringelstein, Marius; Harmel, Jens; Rybak, Jana; Kolbe, Robert; Rhöse, Laura; Gemerzki, Lena; Lee, John‐Ih; Klistorner, Alexander; Guthoff, Rainer; et al.
Abstract: Objective: Studies using conventional full‐field visual evoked potentials (ffVEP) have reported subtle abnormalities in patients with chronic inflammatory demyelinating polyneuropathy (CIDP). We hypothesize that these abnormalities can be detected in the majority of CIDP patients using enhanced methods. Methods: We performed a cross‐sectional noninterventional study comparing 18 CIDP patients and 18 matched healthy controls using multifocal VEP (mfVEP) as a technique with enhanced sensitivity to detect conduction abnormalities across the spectrum of optic nerve fibers. Patients with confounding diseases (ophthalmologic, diabetes mellitus) were excluded. Results: The mean amplitude and latency, as well as the low‐contrast visual acuity, did not differ between CIDP patients and controls. Subanalyses revealed latency differences concerning the superior sector of the visual field. Severity markers of CIDP (ODSS, motor nerve conduction velocity) were associated with mfVEP latency delay. Interpretation: We could not adduce evidence for clinically or diagnostically relevant visual pathway involvement in CIDP. The latency differences identified were very subtle and restricted to the superior visual field which cannot be readily explained biologically, anatomically, or pathologically. In summary, we conclude that our study revealed no relevant differences in mfVEP parameters between CIDP patients and controls.